Pemanfaatan Literasi Digital Berbasis Teknologi Informasi untuk Kesadaran Keamanan Data dan Pencegahan Kejahatan Siber - M. Naufal Ramadhan (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
This research aims to explore the use of information technology-based digital literacy in increasing awareness of data security and preventing cyber crime. The approach used is qualitative with descriptive analysis methods, which combine primary and secondary data. Primary data was obtained through in-depth interviews with information technology experts, digital literacy activists, the government, and the general public, coupled with observations of the implementation of digital literacy programs in several regions. Secondary data was obtained from official documents and reports related to digital literacy and cyber threats. The research results show that although understanding about the use of digital devices is quite widespread, awareness of the importance of protecting personal data is still low. Existing digital literacy programs tend to focus on basic skills in using technology, but do not include material on data security and cyber threats. The main obstacle in implementing digital literacy programs is limited resources and facilities in certain areas. In addition, even though educational efforts regarding cyber threats have been carried out, people still have difficulty understanding the right way to protect their data from cyber attacks. This research concludes that it is necessary to strengthen digital literacy programs that are more inclusive and in-depth, as well as increasing collaboration between the government, the private sector and educational institutions to increase public understanding regarding data security and preventing cyber crime.